(untitled) (Global Journal of Human-Social Science, 2023)
One of the problems affecting children in Mexico is the lack of systematic physical activity which influences school performance For this reason the objective was to determine the effect of an alternative physical activation program to improve school performance This was a quantitative study based on a pre-experimental design The participants were N 134 made up of n 64 boys and n 70 girls the average age was 9 4 1 01 Normality tests were applied as well as Student s t-test to compare the results of Bimesters II and IV the confidence level was 95 with a significance value of p 0 05 The most significant results found were in Mathematics p 0 000 in the second and sixth grades Better progress was obtained with the alternative physical activation program to improve school performance the alternative program was used for 40 sessions with a duration of 45 minutes in advance of the school day In conclusion the alternative physical activation program to improve school performance can have a beneficial effect in the subjects of Mathematics Civic Education and History